High prevalence of epilepsy in onchocerciasis endemic health areas in Democratic Republic of the Congo - Evy Lenaerts (Infectious Diseases of Poverty, 2018)
Abstract Background A high prevalence of epilepsy has been observed in many onchocerciasis endemic regions. This study is to estimate the prevalence of active epilepsy and exposure to Onchocerca volvulus infection in a rural population in Ituri province, Democratic Republic of Congo. Methods In August 2016, a community-based cross-sectional study was conducted in an onchocerciasis endemic area in the rural health zone of Logo, Ituri Province. Households within two neighbouring health areas were randomly sampled. To identify persons with epilepsy, a three-stage approach was used. In the first stage, all individuals of the selected households were screened for epilepsy by non-medical field workers using a validated 5-item questionnaire. In the second and third stage, suspected cases of epilepsy were examined by non-specialist medical doctors, and by a neurologist, respectively. A case of epilepsy was defined according to the 2014 International League Against Epilepsy (ILAE) guidelines. Exposure to O. volvulus was assessed by testing for IgG4 antibodies to an O. volvulus antigen (OV16 Rapid Test,) in individuals aged 3 years and older. Results Out of 1389 participants included in the survey, 64 were considered to have active epilepsy (prevalence 4.6%) (95% confidence interval [CI]: 3.6–5.8). The highest age-specific epilepsy prevalence estimate was observed in those aged 20 to 29 years (8.2%). Median age of epilepsy onset was 10 years, with a peak incidence of epilepsy in the 10 to 15 year-old age group. OV16 test results were available for 912 participants, of whom 30.5% (95% CI, 27.6–33.6) tested positive. The prevalence of OV16 positivity in a village ranged from 8.6 to 68.0%. After adjusting for age, gender and ivermectin use, a significant association between exposure to onchocerciasis and epilepsy was observed (adjusted odds ratio = 3.19, 95% CI: 1.63–5.64) (P < 0.001). Conclusions A high prevalence of epilepsy and a significant association between epilepsy and exposure to O. volvulus were observed in the population in Ituri province, Democratic Republic of Congo. There is an urgent need to implement a CDTI programme and to scale up an epilepsy treatment and care programme.